Concentrations and predictors of aluminum, antimony, and lithium in breast milk: A repeated-measures study of donors. (15th February 2023) - Freire, Carmen; Iribarne-Durán, Luz Maria; Gil, Fernando; Olmedo, Pablo; Serrano-Lopez, Laura; Peña-Caballero, Manuela; Hurtado-Suazo, José-Antonio; Alvarado-González, Nelva E.; Fernández, Mariana F.; Peinado, Francisco M.; Artacho-Cordón, Francisco; Olea, Nicolás
Abstract: Aluminum (Al), antimony (Sb), and lithium (Li) are relatively common toxic metal(oid)s that can be transferred into breast milk and potentially to the nursing infant. This study assessed concentrations of Al, Sb, and Li in breast milk samples collected from donor mothers and explored the predictors of these concentrations. Two hundred forty-two pooled breast milk samples were collected at different times post-partum from 83 donors in Spain (2015–2018) and analyzed for Al, Sb, and Li concentrations. Mixed-effect linear regression was used to investigate the association of breast milk concentrations of these elements with the sociodemographic profile of the women, their dietary habits and utilization of personal care products (PCPs), the post-partum interval, and the nutritional characteristics of milk samples, among other factors. Al was detected in 94% of samples, with a median concentration of 57.63 μg/L. Sb and Li were detected in 72% and 79% of samples at median concentrations of 0.08 μg/L and 0.58 μg/L, respectively. Concentrations of Al, Sb, and Li were not associated with post-partum time. Al was positively associated with total lipid content of samples, weight change since before pregnancy, and coffee and butter intakes and inversely with meat intake. Li was positively associated with intake of chocolate and use of face cream and eyeliner and inversely with year of sample collection, egg, bread, and pasta intakes, and use of hand cream. Sb was positively associated with fatty fish, yoghurt, rice, and deep-fried food intakes and use of eyeliner and inversely with egg and cereal intakes and use of eyeshadow. This study shows that Al, Sb, and Li, especially Al, are widely present in donor breast milk samples. Their concentrations in the milk samples were most frequently associated with dietary habits but also with the lipid content of samples and the use of certain PCPs. Graphical abstract: Image 1 Highlights: Al, Sb, and Li were widely detected in donor milk samples. Concentrations of Al were several times higher than those of Sb and Li. Concentrations of Al, Sb, and Li were associated with dietary habits. Use of certain personal care products was associated with higher Sb and Li.